DETERMINANTS OF FITNESS AFFECTING MORBIDITY FOR HAJJ PILGRIMS IN PALEMBANG - Emma Novita; Mariana Mariana; Achmad Ridwan (Majalah Kedokteran Sriwijaya, 2022)
Indonesia's largest pilgrim in the world where every year more than 220,000 pilgrims and followed by more than 5 million pilgrims in the world. Hajj is a physical worship, namely the congregation must adapt to a crowded environment, extreme hot temperatures, tiring pilgrimages can cause physical fatigue and illness. This study aims to evaluate at the morbidity of the Palembang pilgrims in 2019 so that it can be used to look at the risk factors for outpatient pilgrims and prevent diseases of the pilgrims in the Holy Land. This study was observational Retrospective Cohort design with 2053 outpatient Hajj pilgrims in Mecca and Medina. The results of the analysis of the 5 most outpatient diseases based on ICD X were acute nasopharyngitis (common cold),cough, primary hypertension, ARI, and acute pharyngitis. There was a significant relationship between age and morbidity of primary hypertension, physical fitness with nasopharyngitis, with cough, with hypertension, with acute pharyngitis, with ARI. There was no significant association between gender and disease in pilgrims. The results of the study were that pilgrims were required to maintain fitness with physical exercise and balanced food intake, especially those with comorbid diseases or those who were over 60 years of age.